A Note on Boundary Conditions for the LWR Model - Marušić, Sanja (Promet - Traffic&Transportation, 2012)
The paper studies the boundary conditions for the standard LWR model describing the traffic flow. The notion of the BLN (Bardos, Leroux and Nédélec) condition is described. In the context of traffic flow the BLN conditions have some natural interpretation. The conditions on the density and on the flow and their meaning in real-life situations are discussed. KEY WORDS: LWR model, traffic flow, hyperbolic conservation law, boundary conditions